High‐resolution simulated water balance and streamflow data set for 1951–2020 for the territory of Poland. Issue 2 (28th March 2022) - Marcinkowski, Paweł; Kardel, Ignacy; Płaczkowska, Eliza; Giełczewski, Marek; Osuch, Paweł; Okruszko, Tomasz; Venegas‐Cordero, Nelson; Ignar, Stefan; Piniewski, Mikołaj
Abstract: Long‐term simulated water balance and streamflow data for the territory of Poland with high spatio‐temporal resolution were reconstructed for the period 1951–2020 with a daily time step, using the Soil and Water Assessment Tool (SWAT) hydrological model. The spatial structure includes 4, 381 sub‐basins and 47, 725 hydrological response units. The SWAT model was extensively calibrated and validated following a two‐stage, multi‐site calibration method for 88 gauging stations across Poland. The simulations show satisfactory performance with a median Kling–Gupta efficiency of 0.73 and 0.7 in the calibration and validation period respectively. The model performance exceeded that of its predecessor, the SWAT model of the Vistula and Odra basins. The simulated hydrological data set covers daily water balance components at the sub‐basin level, including precipitation total, snowfall, snowmelt, evapotranspiration (actual and potential), surface runoff, soil water, percolation, groundwater recharge, groundwater flow, tile flow and water yield (all components in mm), and daily streamflow (m 3 /s) at the reach level. The data set is stored in an online, publicly available research data archive 4TU.Research Data (Marcinkowski, P., Kardel, I., Płaczkowska, E., Giełczewski, M., Osuch, P., Okruszko, T., Venegas‐Cordero, N., Ignar, S. & Piniewski, M (2021). PL‐SWAT‐51_20: a high‐resolution simulated water balance and streamflow data set for 1951‐2020 for the territory of Poland, 4TU.ResearchData. dataset, https://doi.org/10.4121/16843183 ). Abstract : Long‐term simulated water balance and streamflow data with high spatio‐temporal resolution for the territory of Poland were reconstructed for the period 1951–2020 with daily time step, using the Soil and Water Assessment Tool (SWAT) hydrological model. Simulated hydrological data set contains daily water balance components at sub‐basin level including precipitation total, snowfall, snowmelt, evapotranspiration (actual and potential), surface runoff, soil water, percolation, groundwater recharge, groundwater flow, tile flow, water yield and daily streamflow.